Effect of combination of garlic powder with black pepper, cinnamon and aloe vera powder on the growth performance, blood profile, and meat sensory qualities of broiler chickens - SINGH, JASWINDER; KAUR, PAVITER; SHARMA, MANJINDER; MEHTA, NITIN; SINGH, N D; SETHI, A P S; SIKKA, S S (The Indian Journal of Animal Sciences, 2020)
This study was conducted to evaluate dual herb combinations as phytogenic alternative to antibiotic growth promoters in broilers. One-day old broiler chicks (225) were randomly distributed to 5 treatments with 3 replicates of each. The dietary treatments comprised basal diet as control (C); antibiotic group receiving 0.1 g/kg of oxytetracycline (AB); 1.5% garlic powder + 0.5% black pepper (GB); 1.5% garlic powder + 0.5% cinnamon powder (GC) and basal diet with 1.5% garlic powder + 1.0% whole leaf aloe vera powder (GA). Body weight and feed consumed were recorded weekly and accordingly feed conversion ratio and protein efficiency ratio were calculated. At the end of 5th week, 2 birds per replicate were sacrificed to determine the carcass characteristics, meat sensory evaluation, blood parameters, duodenum morphology and faecal microbial load. The result revealed that inclusion of herbal combinations improved the weight gain compared to other treatments. All herbal combinations improved the flavour, tenderness and overall acceptability score of meat. Dietary regimen significantly affected the haemoglobin, PCV and TP parameters. Herbal combinations affected the fat digestibility and phosphorus retention, and improved the villus height: crypt depth. It can be concluded that herbal combinations studied have the potential to replace the prevalent antibiotic growth promoters used in broiler chicken.